2017
DOI: 10.1085/jgp.201711850
|View full text |Cite
|
Sign up to set email alerts
|

PnuT uses a facilitated diffusion mechanism for thiamine uptake

Abstract: The bacterial pyridine nucleotide uptake family of transporters mediates the uptake of B-type vitamins, but their transport mechanism is unknown. Jaehme et al. show that the PnuT thiamine transporter utilizes a facilitated diffusion mechanism and supports metabolic trapping of phosphorylated thiamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Therefore, we speculated that the pnuC motif might represent the conserved aptamer domain of a novel riboswitch class that senses and responds to a molecule in the NAD + biosynthetic pathway. However, various homologs of PnuC proteins have been proven to transport other metabolites such as thiamin (PnuT) (Jaehme et al 2018) and riboflavin (PnuX) (Vogl et al 2007), or have been proposed to transport deoxyribonucleosides (PnuN) (Rodionov and Gelfand 2005). The existence of these other proteins left open the possibility that the pnuC genes associated with this novel RNA motif were misannotated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we speculated that the pnuC motif might represent the conserved aptamer domain of a novel riboswitch class that senses and responds to a molecule in the NAD + biosynthetic pathway. However, various homologs of PnuC proteins have been proven to transport other metabolites such as thiamin (PnuT) (Jaehme et al 2018) and riboflavin (PnuX) (Vogl et al 2007), or have been proposed to transport deoxyribonucleosides (PnuN) (Rodionov and Gelfand 2005). The existence of these other proteins left open the possibility that the pnuC genes associated with this novel RNA motif were misannotated.…”
Section: Resultsmentioning
confidence: 99%
“…Values were plotted relative to the logarithm of the molar concentration of ligand, wherein half-maximal binding represents the KD. (Herbert et al 2003), a PnuT thiamin transporter (Jaehme et al 2018), a PnuX riboflavin transporter from Corynebacterium glutamicum (Vogl et al 2007), and a PnuN protein from Lactobacillus acidophilus predicted to transport a deoxynucleoside (Rodionov and Gelfand 2005).…”
Section: In-line Probing Analysesmentioning
confidence: 99%
“…In contrast to the dissolved fraction where B 1 was the most abundant chemical form, within the particulate, B 1 and TMP are present in relatively equal abundances (IQR 47–59% and 34–43% of particulate tB 1 , respectively), and TPP was a minor contributor (IQR 4–12%) to the particulate tB 1 pool. Recently, it has been demonstrated that PnuT‐type transporters can allow passive diffusion of B 1 but not TMP or TPP across cellular membranes (Jaehme et al, ). Therefore, the observed enrichment of particulate B 1 could be the result of passive, diffusion‐based assimilation from the dissolved pool.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to GLUT1, other facilitated diffusion systems have been characterized in JGP , including those for uridine (Cabantchik and Ginsburg, 1977), urea, and ethylene glycol (Mayrand and Levitt, 1983). Very recently, Jaehme et al (2018) demonstrated that facilitated diffusion is the mechanism of thiamine transport through PnuT, a member of the bacterial pyridine nucleotide uptake family; this mechanism is completely different from that of other bacterial thiamine transporters.…”
Section: Simple Carriers or Uniportersmentioning
confidence: 99%